PENGARUH MODEL PEMBELAJARAN BERBASIS E LEARNING DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA BIDANG STUDI PPKn DI KELAS XII.AKUNTANSI SMK SWASTA PANCA DHARMA PADANGSIDIMPUAN TAHUN PELAJARAN 2019-2020 - Ahmad Husein Nasution (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
By analyzing the data with the product moment correlation the results obtained rxy  0.043 or rcount  0.043. If these results are consulted with the critical price list r which has been standardized with N = 30 at the 5% confidence interval of 0.361 and for the 1% confidence interval of 0.463. So that when viewed with rxy  0.043 or rhitung 0.043, smaller than the critical price r 0.043 < 0.361 - 0.463. To find out whether the data is real or not, the writer measures the quality of the data using a helper table provided that if rcount  > rtable  then the tested correlation coefficient is accepted, conversely if rcount  < rtbele then the tested correlation coefficient is rejected. So if 0.043 > 0.361 - 0.463 then the tested correlation coefficient is accepted, conversely if 0.043 < 0.361 - 0.463 then the tested correlation coefficient is rejected. Based on the correlation coefficient tested, it was obtained 0.043 < 0.361- 0.463, meaning that the tested hypothesis was rejected that there was no effect of the e learning-based learning model in increasing student learning interest in the PPKn field of study in Class XII. Accounting at Panca Dharma Padangsidimpuan Vocational High School 2019-2020 Academic Year